Contradições na execução da recuperação de mais-valias fundiárias e do acesso à terra urbana: uma abordagem compreensiva - Luiz Felype Gomes de Almeida (2013)
This work has as main objective to advance the discussion and critical analysis of the limitations related to access to urban land and land recovery gains in economic and legal context of Brazil. Accordingly, we analyze the issue as a starting point, or even the opposition we judge between the social function of property, present in the 1988 Constitution and regulated by the City Statute, and the system of private ownership of land also referenced in our charter. This confrontation, as discussed by Fernandes (2008), is here extended to the economic bias, the recovery of an economic reading and literature, especially the work of Karl Marx in Capital and Ellen Wood (1998) on private property and capitalist as a sponsor role of this mode of production. Done so in order to continue the debate and bringing it in a concrete way the current Brazilian reality in terms of urban policy are presented reflections on the content present in the actual City Statute, regulatory legislation of the constitutional principle discussed initially and contains the main tools recovery gains access to land and urban land currently used in the country. This legal instrument requires such detail here given the way in which it was built and received by the various sectors of Brazilian society involved in the debate on issues related to urban development. Finally, the fourth and final chapter of the dissertation becomes fully concrete and practical issues previously discussed in part or completely through the theoretical case study for the city of Contagem-MG. Since the conclusions are drawn from the observation of a defined territorial physical reality, it is possible to see how the analysis done earlier reproduce in space and are supplemented by other aspects not covered by the study case. How can we verify the implementation of urban policy instruments in the country linked to the regulation of property use bump still many structural barriers and that this scenario is likely to continue if there is a reversal of paths with the aim of a more direct interference on private property . Moreover, it is clear how the political and the contradictions between discourses and practices are established in the territory and are reflected in the composition of urban laws which also contributes to the effectiveness of policies that do not actually seek a reorganization socio-spatial urban in the cities.